1990
DOI: 10.1073/pnas.87.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Holomorphic curves in surfaces of general type.

Abstract: This note answers some questions on holomorphic curves and their distribution in an algebraic surface of positive index. More specifically, we exploit the existence of natural negatively curved "pseudo-Finsler" metrics on a surface S of general type whose Chern numbers satisfy cl > 2c2 to show that a holomorphic map of a Riemann surface to S whose image is not in any rational or elliptic curve must satisfy a distance decreasing property with respect to these metrics. We show as a consequence that such a map ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…As observed by Lu and Yau [LuYa90], one can say more if the topological index c 2 1 −2c 2 is positive, using the following result of Schneider-Tancredi [ScTa85] (the special case when E = T ⋆ X is due to Miyaoka [Miy82]). …”
Section: Of Jets In Irreducible Representationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed by Lu and Yau [LuYa90], one can say more if the topological index c 2 1 −2c 2 is positive, using the following result of Schneider-Tancredi [ScTa85] (the special case when E = T ⋆ X is due to Miyaoka [Miy82]). …”
Section: Of Jets In Irreducible Representationsmentioning
confidence: 99%
“…Especially noticeable in this respect is the work of Dethloff-Wong-Schumacher [DSW92,94] on the hyperbolicity of complements of 3 or more generic curves in the projective plane, and the construction by Masuda-Noguchi [MaNo93] of hyperbolic hypersurfaces of large degree in P n . Also, in a more algebraic setting, there is an extensive literature dealing with the question of computing genus of curves in algebraic surfaces, bearing an intimate connection with hyperbolicity ( [Bog77], [Cle86], [CKM88], [LuYa90], [Lu91], [LuMi95], [Lu96] [Xu94]). Last but not least, there are several important questions of Number Theory which either depend on Nevanlinna theory or suggest new tools for the study of differential geometric problems.…”
Section: §0 Introductionmentioning
confidence: 99%
“…It worth to mention here that on a smooth surface in P 3 , there are no symmetric differentials, by a result of Sakai [13]. Next, as a "second order jet" generalization of some ideas of Miyaoka and Lu-Yau, (see [9,11,14]), Demailly-ElGoul equally show that if the vanishing order of the jet differential is smaller than an explicit number C(d), depending on the degree of the hypersurface, then Theorem 1 follows.…”
mentioning
confidence: 99%
“…Hence, I proposed the following definition to replace the Carathéodory metric. Based on a theorem of Bogomolov, Lu and Yau [7] observed that for an algebraic surface M such that c 2 1 > c 2 , the metric · exists and that either (1) There is a divisor D ⊆ M such that for every holomorphic map f : C → M , the image f (C) ⊆ D ; or (2) There is an algebraic foliation with singularity on M such that f maps C to a leaf of such foliation.…”
Section: Generalized Carathéodory Metricmentioning
confidence: 99%